A method of Fabricating Recycled Carbon Fibre Composite Moudled article - Qumrul, Ahsan; Law, Mei Lin; Noraiham, Mohamad; Rose Farahiyan, Munawar; Hairul Effendy, Ab Maulod; Sivarao, Subramonian (2015)
A method of fabricating a moulded article from a composite material comprising the steps of mixing an epoxy resin and powdered recycled carbon fibre; introducing a curing agent to the mixture; and casting the mixture under vacuum, characterised in that the carbon fibre is treated with a cryogen for sufficient duration over a plurality of cycles at least to remove majority of residual matrix.